A ANALISIS TINGKAT PEMAHAMAN PESERTA DIDIK YANG DIAJARKAN DENGAN METODE EKSPERIMEN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING DI KELAS XI MIA SMA SWASTA HOSANA MEDAN TP. 2019/2020 - Parlindungan Sitorus; Hebron Pardede; Ade Berlian Hulu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2020)
This research was conducted with the aim to improve cognitive, affective and psychomotor understanding of SMA Swasta Hosana Medan students in Class XI MIA odd semester of the 2019/2020 academic year with the subject of elasticity and static fluid with experimental methods using discovery learning models. This research is a classroom action research, which was conducted using two cycles using a total sample. Each class is taught with different teaching material, in the first cycle the teaching material presented is elasticity and in the second cycle the teaching material is static fluid. Each cycle is evaluated, reflected and improved in the hope of achieving cognitive, affective and psychomotor learning indicators for students. From the evaluation results obtained an average cognitive value for cycle I of 70.24 and cycle II of 78.10 with a gain <g> = 0.26 low criteria, and the results of the t test, obtained t count 3.13> t table 1.684 means there is influence. The average affective cycle I was 80.20 while the second cycle was 84.22 with a gain <g> = 0.20 in the low category, and the results of the t test were obtained by t arithmetic 6.203> t table 1.684, meaning that there was an improvement effect of the cycle I to cycle II. For the psychomotor assessment results, the average value of the first cycle was 71.90 while the second cycle was 77.78, and the gain <g> = 0.21 was in the low category, and from the results of the t test, t count was 7.83> t table 1.684 there is an improvement in the results from cycle I to cycle II. Thus the level of understanding of SMA Swasta Hosana Medan students in class XI MIA increases if taught by the experimental method using discovery learning models for the subject matter of elasticity and static fluid in the 2019/2020 academic year.